Gestión de riesgos financieros: experiencia en un banco latinoamericano - Lizarzaburu, Edmundo R. (2012)
The present document attempts to present the basic concepts of financial risk present in a bank, and in particular will present the case of a Peruvian bank, taking into accounts aspects such as risk management, the Third Basel Accord (Basel III) and the international financial crisis. The case was developed in the last quarter of 2012 in the Peruvian market.